Association Analysis of SSR Markers with Phenology, Grain, and Stover-Yield Related Traits in Pearl Millet (Pennisetum glaucum (L.) R. Br.) - Baskaran Kannan (The Scientific World Journal, 2014)
Pearl millet is a staple food crop for millions of people living in the arid and semi-arid tropics. Molecular markers have been used to identify genomic regions linked to traits of interest by conventional QTL mapping and association analysis. Phenotypic recurrent selection is known to increase frequencies of favorable alleles and decrease those unfavorable for the traits under selection. This study was undertaken (i) to quantify the response to recurrent selection for phenotypic traits during breeding of the pearl millet open-pollinated cultivar “CO (Cu) 9” and its four immediate progenitor populations and (ii) to assess the ability of simple sequence repeat (SSR) marker alleles to identify genomic regions linked to grain and stover yield-related traits in these populations by association analysis. A total of 159 SSR alleles were detected across 34 selected single-copy SSR loci. SSR marker data revealed presence of subpopulations. Association analysis identified genomic regions associated with flowering time located on linkage group (LG) 6 and plant height on LG4, LG6, and LG7. Marker alleles on LG6 were associated with stover yield, and those on LG7 were associated with grain yield. Findings of this study would give an opportunity to develop marker-assisted recurrent selection (MARS) or marker-assisted population improvement (MAPI) strategies to increase the rate of gain for pearl millet populations undergoing recurrent selection.